2020
DOI: 10.33223/epj/127921
|View full text |Cite
|
Sign up to set email alerts
|

Development of the US electric car market: macroeconomic determinants and forecasts

Abstract: In the article, mathematical modeling methods are used to study the main trends and macroeconomic determinants of the electric car market development in 2011-2018 on the example of the US. The determinants include economic (GDP), socioeconomic (household income), energy (electricity use), and environmental (СО 2 emissions) factors. The authors justify the role of electric transport in strengthening national energy security due to the transition to renewable energy technologies and the reduction of fossil fuel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…It was found that with reduced consumption of energy resources, enterprises may have higher profitability, as reduced energy costs directly lead to increased profits. Sotnyk et al (2020) substantiate the role of electric transport in strengthening national energy security through the transition to renewable energy technologies and reducing the use of fossil fuels. Burlov et al (2021) substantiated the mathematical model of the region energy sector management, which was based on three main system-forming indicators of social, economic and environmental systems.…”
Section: Literature Reviewmentioning
confidence: 92%
“…It was found that with reduced consumption of energy resources, enterprises may have higher profitability, as reduced energy costs directly lead to increased profits. Sotnyk et al (2020) substantiate the role of electric transport in strengthening national energy security through the transition to renewable energy technologies and reducing the use of fossil fuels. Burlov et al (2021) substantiated the mathematical model of the region energy sector management, which was based on three main system-forming indicators of social, economic and environmental systems.…”
Section: Literature Reviewmentioning
confidence: 92%
“…We will give a brief description of the main elements of the information system of regional management, which are relevant in the formats of practical development and a further improvement in the knowledge system of regional information management, providing the involvement of knowledge management approaches [9][10][11][12][13][14].…”
Section: Creation Of a Specialised Automated Information Systemmentioning
confidence: 99%
“…It covers the economic and management aspects of electric car production and operation and technical, environmental issues, etc. Today, electric transport includes passenger cars, city and intercity buses, trucks (Sotnyk et al, 2020). The organizer of public transport is also responsible for the periodic control and assessment of the opera-tors and the carriers' services, encompassing the compliance with the rules of the operating public transport.…”
Section: Literature Reviewmentioning
confidence: 99%